Stability of cervical spine after one-level corpectomy using different numbers of screws and plate systems - Abdul Kadir, Mohammed Rafiq (Professional Engineering Publishing, 2014)
Anterior corpectomy and reconstruction using a plate with locking screws are standard procedures for the treatment of cervical spondylotic myelopathy. Although adding more screws to the construct will normally result in improved fixation stability, several issues need to be considered. Past reports have suggested that increasing the number of screws can result in the increase in spinal rigidity, decreased spine mobility, loss of bone and, possibly, screw loosening. In order to overcome this, options to have constrained, semi-constrained or hybrid screw and plate systems were later introduced. The purpose of this study is to compare the stability achieved by four and two screws using different plate systems after one-level corpectomy with placement of cage. A three-dimensional finite-element model of an intact C1-C7 segment was developed from computer tomography data sets, including the cortical bone, soft tissue and simulated corpectomy fusion at C4-C5. A spinal cage and an anterior cervical plate with different numbers of screws and plate systems were constructed to a fit one-level corpectomy of C5. Moment load of 1.0 N m was applied to the superior surface of C1, with C7 was fixed in all degrees of freedom. The kinematic stability of a two-screw plate was found to be statistically equivalent to a four-screw plate for one-level corpectomy. Thus, it can be a better option of fusion and infers comparable stability after one-level anterior cervical corpectomy, instead of a four-screw plate.